Experimental study of heat distribution in a Non-uniform heat source of a natural circulation loop. (July 2022) - Bello, Solomon; Gao, Puzhen; Abiodun Olatubosun, Samuel; Lin, Yuqi; Njoroge, John
Highlights: Single-phase flow behaviors in a natural circulation system have been studied. An axially truncated heated channel installed in a modified closed rectangular natural circulation loop has been investigated. Irregular heat distributions associated to the non-uniform channel were analyzed for different heating powers at low system pressure. Transitions in heat peaking along the axially heated section of the non-uniform heat distribution were discussed. Abstract: An experimental investigation has been carried out on heat distribution in a non-uniform heating channel of a natural circulation (NC) loop under single-phase condition. A heated channel with a truncated axial cosine heat flux distribution was used in the NC circuit and the non-uniformity of the channel is defined in its outer dimension which is convex in shape. The NC experimental loop similar to the primary loop of a Pressurized Water Reactor (PWR) was first reviewed and adjusted to determine the various critical positions for the thermocouples along the heated and flow channels. The experimental procedures involve setting the heating channel inlet temperature at different heating power, followed by observation of the thermal hydraulic responses. When a stable flow is achieved at each inlet parameters, data are recorded till the onset of flow instability. The findings through the results obtained, extend the knowledge on adoption of the NC systems and contribute to a better understanding of the impact of irregular heat distribution on heat transfer capability of the NC loop.